Can smallholder farmers adapt to climate variability, and how effective are policy interventions? Agent-based simulation results for Ethiopia - Berger, T.; Troost, C.; Assfaw Wossen, Tesfamicheal; Latynskiy, E.; Tesfaye, K.; Gbegbelegbe, Sika (Wiley, 2017)
Climate variability with unexpected droughts and floods causes serious production losses and worsens food security, especially in Sub-Saharan Africa. This study applies stochastic bioeconomic modeling to analyze smallholder adaptation to climate and price variability in Ethiopia. It uses the agent-based simulation package Mathematical Programming-based Multi-Agent Systems (MPMAS) to capture nonseparable production and consumption decisions at household level, considering livestock and eucalyptus sales for consumption smoothing, as well as farmer responses to policy interventions. We find the promotion of new maize and wheat varieties to be an effective adaptation option, on average, especially when accompanied by policy interventions such as credit and fertilizer subsidy. We also find that the effectiveness of available adaptation options is quite different across the heterogeneous smallholder population in Ethiopia. This implies that policy assessments based on average farm households may mislead policy makers to adhere to interventions that are beneficial on average albeit ineffective in addressing the particular needs of poor and food insecure farmers.